Методика синтезу звуку бас-барабану - Капленко, М. В. (ХНУРЕ, 2025)
Kick drum is the main rhythmic element in most electronic compositions. Its structure consists of an attack, a body, and noise components, each of which determines the character of the sound. The main body is usually formed by a sinusoidal wave, and the attack is created by a pulse signal or noise burst. Processing includes compression, equalization, saturation, and dynamic correction to improve sound quality. Final mixing strikes a balance between kick-drum and bass in the mix, using sidechain compression to harmonize low-frequency elements.
Keywords: звук бас-барабану; синтезу звуку